Geotrichum capitatum septicemia in a hematological malignancy patient with positive galactomannan antigen: case report and review of the literature - Özkaya-Parlakay, Aslınur; Cengiz, Ali Bülent; Karadağ-Öncel, Eda; Kuşkonmaz, Barış; Sarıbaş, Zeynep; Kara, Ateş; Oğuz, Berna (The Turkish Journal of Pediatrics, 2012)
Geotrichum capitatum, formerly known as Trichosporon capitatum, is an uncommon but frequently fatal invasive fungal infection in immunocompromised patients, especially in hematological malignancies. We report a seven-year-old patient with acute myeloid leukemia with Geotrichum septicemia with involvement of the lungs, liver, spleen, and kidneys, who had a favorable outcome after therapy. Alteration of antifungal treatment to liposomal amphotericin B resolved the fever with favorable clinical response.